2010
DOI: 10.1007/s13157-010-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Growth, Carbon Allocation and Nutrient Budgets of Phragmites australis in Lake Burullus, Egypt

Abstract: Phragmites australis is the major component of reed stands covering some 8200 ha along the shores of Lake Burullus (Egypt). We applied a published temperate zone reed model to assess growth and cycling of C and nutrients among the various organs of P. australis in this sub-tropical lake. We aim to quantify the role of reed stands for the C balance and nutrients cycling in the south Mediterranean wetland. Above-ground biomass was 3.5 times higher than the below-ground biomass. Root biomass represented 13% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…This finding is supported by our previous study on Eichhornia crassipes (Eid & Shaltout 2017), which indicated that the gross and net production of E. crassipes populations were higher in the tropical and sub-tropical regions than in the Nile Delta (Mediterranean region). Since biomass is often largely determined by specific habitat conditions (Luther 1983), the high biomass in the tropical and sub-tropical regions could be due to environmental factors that vary with latitude such as temperature, day length, solar irradiance, and length of growing season (Sand-Jensen 1989;Eid et al 2010Eid et al , 2013. Variation may also be partly attributed to biotic factors such as mutualists/facilitators or predators/pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by our previous study on Eichhornia crassipes (Eid & Shaltout 2017), which indicated that the gross and net production of E. crassipes populations were higher in the tropical and sub-tropical regions than in the Nile Delta (Mediterranean region). Since biomass is often largely determined by specific habitat conditions (Luther 1983), the high biomass in the tropical and sub-tropical regions could be due to environmental factors that vary with latitude such as temperature, day length, solar irradiance, and length of growing season (Sand-Jensen 1989;Eid et al 2010Eid et al , 2013. Variation may also be partly attributed to biotic factors such as mutualists/facilitators or predators/pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Also it receives fish farms and industrial drainage water [18]. It is alkaline, shallow, brackish, and polluted lake [8]. The Mediterranean deltaic coast, in which this lake occurs, belongs to the arid region where the climatic conditions are warm summers (20˚C -30˚C) and mild winters (10˚C -20 ˚C).…”
Section: Study Areamentioning
confidence: 99%
“…Specifically, plants with potentially high annual primary production can extract large amounts of heavy metals from their environment and store these metals in biomass and litter [8]. Therefore, some aquatic plants such as Eichhornia crassipes (C.…”
Section: Introductionmentioning
confidence: 99%
“…Reed beds, along the deltaic Mediterranean coast of Egypt, are important for wintering, foraging, refuge, and breeding of the migrant birds (Kassas 2002). Also, these stands probably play an important role in the nutrient budget of the Mediterranean coastal waters and lakes (Eid et al . 2010a,b).…”
Section: Introductionmentioning
confidence: 99%
“…1997), and it provides important information on wetland functioning (nutrient cycling and energy flow; Robinson & Gessner 2003). Phragmites australis occupies about 20% of Lake Burullus area (= 8200 ha) with a high primary production on the order of 54 t/ha (Eid et al . 2010b).…”
Section: Introductionmentioning
confidence: 99%